2002
DOI: 10.1093/nar/gkf688
|View full text |Cite
|
Sign up to set email alerts
|

Integrity of duplex structures without hydrogen bonding: DNA with pyrene paired at abasic sites

Abstract: DNA polymerases specifically insert the hydrophobic pyrene deoxynucleotide (P) opposite tetrahydrofuran (F), an stable abasic site analog, and DNA duplexes containing this non-hydrogen-bonded pair possess a high degree of thermodynamic stability. These observations support the hypothesis that steric complementarity and stacking interactions may be sufficient for maintaining stability of DNA structure and specificity of DNA replication, even in the absence of hydrogen bonds across the base pair. Here we report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
75
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 30 publications
(18 reference statements)
4
75
0
3
Order By: Relevance
“…The effects of sterics, stacking, hydrogen bonding, and minor-groove solvation have been considered as contributing factors. [1][2][3][4] Probably the dominant stabilizing factor in helical DNA is base stacking. [5,6] In order to probe the physical factors that contribute to the stability of this stacking in water, measured melting data of short DNA oligomers, both naturally and nonnaturally substituted, has been studied.…”
mentioning
confidence: 99%
“…The effects of sterics, stacking, hydrogen bonding, and minor-groove solvation have been considered as contributing factors. [1][2][3][4] Probably the dominant stabilizing factor in helical DNA is base stacking. [5,6] In order to probe the physical factors that contribute to the stability of this stacking in water, measured melting data of short DNA oligomers, both naturally and nonnaturally substituted, has been studied.…”
mentioning
confidence: 99%
“…Planar aromatic molecules are often examined because the compounds have high potential for the stacking interaction and may intercalate between base pairs in a duplex. 25,26 Notably, it is reported that even a very large aromatic group such as pyrene 27 and porphyrin 28 increases the duplex stability.…”
Section: Extraction Of "New Quality" From the Quantity Of Dnamentioning
confidence: 99%
“…Examples of scaffolds for bringing together multiple light-absorbing and -emitting species include dendrimers, [1] peptide backbones, [2] hydrocarbon frameworks, [3] organic polymer backbones, [4] and DNA. [5] In the last category, we have prepared DNA-like oligomers in which DNA bases are replaced by fluorescent chromophores.…”
Section: Introductionmentioning
confidence: 99%